Better behavioral control in sharia investment decision: a literature review - Surendra Purusottama Rangga; Y Anni Aryani; Doddy Setiawan; Ibrahim Fatwa Wijaya; Setiyawan Gunardi (UIN Walisongo Semarang, 2026)
Non-Indexed Publication